Studi Pemisahan Thorium dari Besi dan Logam Tanah Jarang dalam Larutan Asam Nitrat dengan Ekstraksi Pelarut Menggunakan Ekstraktan Trioctylphosphine Oxide - Briliant Briliant; Mubarok, Mohammad Zaki; Trinopiawan, Kurnia; Prassanti, Riesna (BRIN Publishing, 2017)
A series of solvent extraction experiment to separate thorium(Th) from iron (Fe) and rare earth metals (REE) using trioctylphosphine oxide (TOPO) conducted with variations of nitric acid concentration, extraction time, ratio between exctractan and diluent (g/mL), and ratio between organic solution and aqueous solution volumes (O/A), and variation of nictric acid concentration in stripping process. Thorium, iron and rare earth metals early concentration in solution feed were measured by using Inductively Coupling Plasma (ICP), Atomic Absorption Spectroscopy (AAS), dan Ultraviolet Visible Spectroscopy (UV-VIS Spectro) respectively. The nitric acid concentration was varied at 1M, 2M, 3M, 4M, and 5M. The extraction time was varied at 2, 5, 10, 15, and 20 minutes, meanwhile the ratio between extractan and diluent (g/mL) was varied at 2:100, 3:100, 4:100, 5:100, and 6:100 with O/A ratio at 1:3, 1:2, 1:1, 2:1, and 3:1. At stripping stage, the nitric acid concentration was varied at 0.1M; 0.2M; 0.3M; 0.4M; and 0.5M. The result of the experiments show that the best condition was obtained on 3M nitric acid concentration, 10 minutes extraction time, 5:100 (g/mL) extractan and diluent ratio, and 1:1 O/A ratio, that resulted in 97.26% Th extraction, 7.97% Fe extraction, and 62.15% rare earth metals extraction with βTh-Fe and βTh-REE value 273.62 and 14.43 respectively. On the stripping experiment, the highest Th stripping percentage obtained as much as 51.37% at 0.3M nitric acid concentration with Fe and REE stripping percentage up to 2.72% and 2.55% respectively.